Optimisation and application of dispersive liquid-liquid microextraction for simultaneous determination of carbamates and organophosphorus pesticides in waters - Raquel Sousa (2013)
A very simple and sensitive method was developed for the simultaneous determination of carbamate and organophosphorus pesticides in water samples, using dispersive liquid-liquid microextraction (DLLME) coupled with gas chromatography-mass spectrometry (GC-MS). Carbofuran and chlorfenvinphos were used as model molecules in this study. The optimisation of some important DLLME parameters (type and volume of extraction and dispersive solvents, sample volume, extraction time, and use of NaCl) was performed using a design of experiments approach. Under optimised conditions of the DLLME methodology (500 mu L of methanol, 80 mu L of chlorobenzene, 10 mu L of aqueous sample, 4 minutes of vortexing and no salt addition), the calibration curve was linear in the concentration range of 0.1-250 mu g L-1 for carbofuran and 0.1-200 mu g L-1 for chlorfenvinphos. The limits of detection (LODs) were 0.04 mu g L-1 for the carbamate and 0.02 mu g L-1 for the organophosphorus pesticide. The proposed method was successfully applied to the analysis in river, mineral and tap water samples, yielding satisfactory results.